Socioeconomic characterization of environments and technologies - Smith, J. (1995)
Socioeconomic characterization provides information for setting research priorities, extrapolating research results, and targeting existing technologies to appropriate areas. Farmers adopt technologies which economize scarce, and hence, expensive resources, and make use of abundant, cheap resources. This document divides environments into three categories, based on combinations of population density and access to markets, and identifies types of technologies likely to be appropriate in each category.